The Effect of Profitability and Institutional Ownership on Firm Value with Firm Size as a Moderating Variable - Annisa Firmansyah; Khairunnisa Khairunnisa (Universitas KH. Abdul Chalim Mojokerto, 2026)
Firm value reflects market perceptions of a company’s performance and future prospects, which are commonly associated with stock prices. This study aims to analyze the effects of profitability and institutional ownership on firm value, with firm size serving as a moderating variable. The research is motivated by the declining trend in the average Tobin’s Q ratio of food and beverage companies listed on the Indonesia Stock Exchange during the 2020-2024 period, indicating weakening market valuation within the subsector. This study employs a quantitative approach using Moderated Regression Analysis (MRA). The sample consists of 31 food and beverage companies selected through purposive sampling, resulting in 155 firm-year observations. The results show that profitability has a positive and significant effect on firm value, while institutional ownership does not have a significant effect. Furthermore, firm size strengthens the effect of profitability on firm value but does not moderate the relationship between institutional ownership and firm value. This study contributes to the development of signaling theory by examining the moderating role of firm size in the post-pandemic period and provides practical implications for investors and companies in evaluating firm value.